Contributions to the knowledge of southern South American species of Astylus Laporte, 1836 (Coleoptera: Melyridae). Re-describing Astylus vittaticollis (Blanchard, 1843) and A. patagonicus (Blanchard, 1843) - Estrada M., Patricia (Zootaxa, 2020)
Knowledge of the Astylus genus has been limited to descriptions of species and catalogs without a taxonomic review, except for the contributions of Pic (1902, 1919a, b) and Champion (1918), who studied groups of species comparing morphological characters. In the present work, Astylus vittaticollis (Blanchard, 1843) and A. patagonicus (Blanchard, 1843) are redescribed based on the study of their types and additional material. As a result, the synonymy between A. patagonicus and A. steinheili Estrada, 2016 is recognized.